The Relationship of Anxiety Level with the Success of the Process in Particular Mothers in the Active Phase I of Primigravida - Betanuari Sabda Nirwana; Alfika Awatiszahro; Rahma Kusuma Dewi (Universitas STRADA Indonesia, 2021)
Anxiety appears in the third trimester (28-40 weeks) starting before delivery. In addition, this third trimester is a high risk of the possibility of premature birth so that it can cause high anxiety in primigravida mothers. One of the factors that need attention is the maternal factor, namely the level of anxiety in the face of childbirth. One of the indicators of anxiety is anxiety, fear and stress. And if not handled, the consequences will have a negative impact which can lead to new problems. This study aims to determine whether there is a relationship between anxiety levels and the smooth delivery of primigravida inpartu mothers at Gemarang Health Center, Ngawi Regency. The research design used is cross sectional. The population in this study were all primigravida mothers at Gemarang Health Center, with a total population of 30 primigravida mothers. Samples were taken in this study through inclusion and exclusion criteria with data analysis coding, scoring and tabulating. The results of the study showed that there was a relationship between anxiety in facing childbirth with smooth delivery in primigravida inpartu mothers at Gemarang Health Center, Ngawi Regency in 2021 (p value = 0.003). Where there is a relationship between anxiety in facing labor and smooth delivery in primigravida inpartu mothers due to an anxious condition, a mother cannot concentrate on the labor process she is facing. This condition at a later stage will reduce power or his so that it will increase the time of delivery because the fetus is not born immediately. On the other hand, when the mother is calm, the mother can gather strength for the physiological process of labor to take place.